Review on process validation of Amoxicillin Potassium Clavulanate Dry Syrup - Devi, Anjana; Kumar, Sanjay; Jeet, Kamal; Sharma, Vikash; Chaudhary, Aman (Asian Journal of Pharmaceutical Research and Development, 2022)
Modern medicines for human use are required to comply with specific standards and regulation set forth by the concerned authorities. A simple and sensitive UV spectrophotometric method was developed and validated for the simultaneous determination of Potassium Clavulanate (PC) and Amoxicillin. As complementary of this work, an assay method for amoxicillin and potassium clavulanate mixtures was developed and validated; stress-testing and stability studies of amox/clav mixtures was carried out under specified conditions according to ICH and analyzed by using validated stability-indicating assay and related substances methods. Aim of this study was to test the validation of derivative spectrophotometric method in simultaneous determination the content amoxicillin and clavulanate potassium in dry syrup by derivative spectrophotometric method with zero crossing technique, in buffer phosphate pH 4,4-methanol (91:9) mixture.